Preparation method of dynamic micron-sized gel powder and instant-to-use dynamic hydrogel
By preparing dynamic micron-scale gel powder, using nanocomposite hydrogel technology with multiple dynamic bond crosslinking, the problem of cumbersome preparation of dynamic hydrogels and the need for cold chain transportation is solved, realizing the effect of instant use and simplifying storage and transportation .
Patent Information
- Application Number
- CN202411543813.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, the preparation of dynamic hydrogels is cumbersome and time-consuming, and it is necessary to maintain a low-temperature sterile environment during transportation, resulting in expensive facilities, high energy consumption and complex procedures.
By preparing dynamic micron-scale gel powder, using materials such as oxidized hyaluronic acid, carbohydrazide modified gelatin and polydopamine nanoparticles, a nanocomposite hydrogel with multiple dynamic bonds crosslinking is formed, and the coagulation is obtained by freeze-drying and grinding. Glue powder can be stored for a long time under ambient conditions and quickly hydrates to form a dynamic hydrogel when needed.
It realizes the immediate use of dynamic hydrogels, avoids the need for cold chain management, simplifies the storage and transportation process, and retains the self-healing, injectable and mechanical properties of the hydrogels.
Smart Images

Figure CN119386283A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical material development, and relates to a dynamic micron-grade gel powder and a method for preparing an instant dynamic hydrogel. Background Art
[0002] Injectable hydrogels can be combined with minimally invasive interventional therapy techniques to implant bioactive substances such as cells, drugs, and growth factors at the target lesions, and utilize the properties of the material itself, such as swelling, biodegradation, and environmental response, to slowly release these bioactive substances, with the characteristics of less trauma, precise treatment, and rapid postoperative recovery. However, it is difficult for traditional injectable hydrogels to achieve precise control of the sol-gel transition, leading to problems such as needle clogging, loss of bioactive substances, and biological contamination. In order to solve these problems, dynamic self-healing injectable hydrogels with shear-thinning and structural reversible properties have emerged. Its advantage is that the gel state can be directly manipulated, which changes the fluid manipulation method of traditional injectable hydrogels. First, the gel is formed in situ in the syringe, and the stress generated during injection induces shear-thinning of the hydrogel, which facilitates the injection of the gel into the target site. Subsequently, the extruded gel particles self-heal and reshape and restore the original structure and function of the hydrogel through the interaction of dynamic bonds. Generally, dynamic hydrogels are applied in the form of a gel state that swells a large amount of solution in a viscoelastic polymer network. However, the preparation of dynamic hydrogels often involves chemical synthesis and purification. The whole process is cumbersome and time-consuming, and cannot meet the needs of immediate use. At the same time, the storage and transportation of hydrogels in a hydrated state must follow the principle of sterility in a low temperature or even frozen environment to avoid bacterial invasion and biodegradation. Although cold chain management is currently the best solution for storing and transporting hydrogels in a hydrated state, there are still problems such as expensive facilities, high energy consumption and complicated procedures. Therefore, how to quickly and conveniently obtain dynamic hydrogels while avoiding the use of cold chain management is an urgent problem to be solved. At present, the hydrogels disclosed in powder form are mainly aimed at problems such as wound bleeding and postoperative adhesion. The raw materials for preparing hydrogels are processed into powders and mixed. When used, they are hydrated in situ at the site of action to form a hydrogel barrier. However, the above method does not involve the preparation of dynamic micron-sized gel powders, storage and transportation under ambient conditions, and the immediate use of dynamic hydrogels and the delivery of drugs (such as proteins). Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a dynamic micron-sized gel powder and a method for preparing a ready-to-use dynamic hydrogel, thereby solving the technical problems in the prior art that the water-containing hydrogel must maintain a low-temperature sterile environment during transportation, and that a ready-to-use dynamic self-healing injectable hydrogel cannot be directly prepared from a powder state.
[0004] The present invention is achieved through the following technical solutions: A method for preparing dynamic micron-sized gel powder comprises the following steps: S1: dissolving dopamine hydrochloride in a Tris-HCl buffer containing a protein to be carried, stirring the reaction, and preparing protein-loaded polydopamine nanoparticles; S2: dissolving oxidized hyaluronic acid in a phosphate buffer solution, and adding the protein-loaded polydopamine nanoparticles to obtain an oxidized hyaluronic acid solution containing nanoparticles; dissolving carbohydrazide-modified gelatin in a phosphate buffer solution containing borax to obtain a carbohydrazide-modified gelatin / borax solution; S3: uniformly mixing the oxidized hyaluronic acid solution and the carbohydrazide-modified gelatin / borax solution to prepare a nanocomposite hydrogel based on multiple dynamic bond crosslinking; S4: freeze-drying and grinding the multiple dynamic bond cross-linked nanocomposite hydrogel to obtain the dynamic micron-sized gel powder.
[0005] Preferably, in step S1, the mass concentration of dopamine hydrochloride is 0.2-10 mg / mL; the mass concentration of the protein to be carried in the Tris-HCl buffer is 0.5-3 mg / mL; during the stirring reaction, the stirring speed is 100-600 rpm, and the reaction time is 8-24 h.
[0006] Preferably, in step S2, the preparation of the carbohydrazide-modified gelatin is as follows: heating gelatin to dissolve in deionized water, adding carbohydrazide, and adding N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole hydrate after the gelatin is completely dissolved, then adjusting the pH value of the system to 5, carrying out an amidation reaction at room temperature, and finally obtaining the carbohydrazide-modified gelatin after dialysis and freeze-drying; the mass ratio of the gelatin, carbohydrazide, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, and 1-hydroxybenzotriazole hydrate is (2.5~3.2):(2.0~2.5):(0.42~0.48):(0.43~0.50); and the amidation reaction time is 12~24 h.
[0007] Preferably, in step S2, the concentrations of the oxidized hyaluronic acid and the carbohydrazide-modified gelatin / borax solution are 3 wt% to 15 wt% and 10 wt% to 12 wt%, respectively.
[0008] Preferably, in step S3, the volume ratio of the oxidized hyaluronic acid solution containing nanoparticles to the carbohydrazide-modified gelatin / borax solution is 1:(1.5-2.5).
[0009] Preferably, in step S3, the gelation temperature of the nanocomposite hydrogel is 37 °C, and the gelation time is 5 to 30 s.
[0010] A dynamic micron-sized gel powder is prepared by the above method; the average pore size of the gel powder is 50 μm.
[0011] The method for using the above-mentioned dynamic micron-sized gel powder is to add an appropriate amount of water to the dynamic micron-sized gel powder to form an injectable water-containing hydrogel after complete hydration.
[0012] Preferably, the ratio of water to dynamic micron-sized gel powder is (5.67-8.09) g:1.0 g.
[0013] Preferably, the hydration time is 5 to 90 min.
[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a preparation method of dynamic micron-sized gel powder. In the method, aldehyde groups on oxidized hyaluronic acid macromolecular chains and amino groups on carbohydrazide-modified gelatin macromolecular chains undergo Schiff base reaction to generate acylhydrazone bonds, tetraborate ions react with oxidized hyaluronic acid to generate borate bonds, and polydopamine nanoparticles are doped in the gel network as nano cross-linking agents to form hydrogen bonds with biological macromolecules. Therefore, the acylhydrazone bonds, borate bonds and hydrogen bonds in the system together enable the hydrogel to have good self-healing, injectable, mechanical properties and anti-fatigue properties. In the preparation process, the protein is fixed by the Michael addition reaction between dopamine hydrochloride and amino acid residues on a protein to be carried during the oxidative self-polymerization process, and the self-healing injectable hydrogel is endowed with a protein sustained-release function. In addition, when the prepared dynamic micron-sized gel powder is used, it only needs to add an appropriate amount of solution to quickly hydrate and form a dynamic gel, which can not only meet the requirements of instant use in biomedicine and clinical operations and effectively realize the delivery of protein drugs, but also avoid batch performance differences during the preparation of dynamic hydrogels through a standardized preparation process. The dynamic micron-sized gel powder can be quickly hydrated after being added into an aqueous solution to form a hydrogel with self-healing properties, which enables ready-to-use preparation and convenient transportation and storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0016] Figure 1 It is a schematic flow chart of a method for preparing a dynamic micron-sized gel powder that can be stored and transported for a long time under ambient conditions and using the same in the present invention; Figure 2A The infrared spectra of hyaluronic acid, oxidized hyaluronic acid, gelatin and carbohydrazide-modified gelatin are shown; Figure 2B The infrared spectra of dopamine hydrochloride, polydopamine nanoparticles, nanocomposite hydrogel, bovine serum albumin and protein-loaded polydopamine nanoparticles; Figure 3 is the compressive strain-stress curve of the nanocomposite hydrogel; Figure 4A This is a graph showing the macroscopic self-healing test results of nanocomposite hydrogel; Figure 4B is the self-healing efficiency of the nanocomposite hydrogel after healing at 37 °C for 1 h; Figure 5A The figure shows the injectability and stability test results of the nanocomposite hydrogel; Figure 5B The viscosity response test results of nanocomposite hydrogel (constant strain 1%, angular frequency 0.1 -100 rad / s); Figure 6 This is a scanning electron microscope image of dynamic micron-sized gel powder; Figure 7 A physical picture of the gel powder and a macroscopic display of the powder hydration to form a dynamic gel; Figure 8 is the scanning electron microscope image of the hydrated dynamic gel; Fig. 9 Compressive strain-stress curves of dynamic gels formed by hydration of gel powders stored for different times; Fig.10 The figure is a test result diagram of the injectability and stability of the hydrated dynamic gel; Fig.11A The UV-visible absorption spectra of bovine serum albumin, polydopamine nanoparticles and protein-loaded polydopamine nanoparticles at pH 7.4; Fig. 11B The scanning electron microscope images of polydopamine nanoparticles and protein-loaded polydopamine nanoparticles; Fig. 11C The zeta potential test results of polydopamine nanoparticles and protein-loaded polydopamine nanoparticles; Fig.11D The particle size test results of polydopamine nanoparticles and protein-loaded polydopamine nanoparticles; Fig.12The cumulative release test results of BSA from dynamic gels formed by hydration of original nanocomposite hydrogels and gel powders stored for different times; Fig.13A Live / dead staining images of mouse L929 fibroblasts cultured in hydrogel extract for 24, 48, and 72 h; Fig. 13B The results of cell viability detection using a cell viability detection kit (CCK-8). DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0018] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0019] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0020] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0021] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0022] like Figure 1 As shown, the present invention provides a method for preparing a dynamic micron-sized gel powder that can be stored and transported for a long time under ambient conditions, comprising the following steps: S1: dissolving 0.2-10 mg / mL dopamine hydrochloride in a Tris-HCl buffer (pH 8.5) containing bovine serum albumin, stirring the mixture at a speed of 100-600 rpm for 8-24 h to obtain protein-loaded polydopamine nanoparticles; the mass concentration of bovine serum albumin in the Tris-HCl buffer is 0.5-3 mg / mL; S2: dissolving oxidized hyaluronic acid in a phosphate buffer solution with a concentration of 0.1 mol / L and a pH of 7.4 to obtain an oxidized hyaluronic acid solution with a mass percentage of 3 wt%~15 wt%; dispersing protein-loaded polydopamine nanoparticles in the hyaluronic acid solution to obtain an oxidized hyaluronic acid solution containing nanoparticles with a mass concentration of 0.1~12 mg / mL; dissolving carbohydrazide-modified gelatin in a phosphate buffer solution containing borax to obtain a carbohydrazide-modified gelatin / borax solution with a mass percentage of 10 wt%~12 wt%; wherein the concentration of borax in the carbohydrazide-modified gelatin / borax solution is 0.1 mol / L; S3: The oxidized hyaluronic acid solution containing nanoparticles is mixed evenly with the carbohydrazide-modified gelatin / borax solution to prepare a nanocomposite hydrogel based on multiple dynamic bond crosslinking; during the mixing process, the volume ratio of the oxidized hyaluronic acid solution containing nanoparticles to the carbohydrazide-modified gelatin / borax solution is 1:(1.5-2.5). The gelation temperature of the nanocomposite hydrogel is 37 °C, and the gelation time is 5-30 s.
[0023] S4: freeze-drying the multiple dynamic bond cross-linked nanocomposite hydrogel at -60 to -80 °C for 48 to 96 h, and then grinding the nanocomposite hydrogel until no particles are visible to the naked eye, thereby obtaining a dynamic micron-sized gel powder that can be stored and transported for a long time under ambient conditions; The storage and transportation environment conditions of the dynamic micron-sized gel powder are a temperature of 15-25°C and a humidity of 40%RH-70%RH.
[0024] After long-term storage under ambient conditions, the gel powder can be used to quickly hydrate and form a dynamic gel by directly adding an appropriate amount of solution to the dynamic micron-sized gel powder; during the hydration process, the ratio of the added solution to the gel powder is (5.67-8.09) g:1.0 g. The time for the rapid hydration is 5-90 min.
[0025] Specifically, the method for preparing the oxidized hyaluronic acid in step S2 comprises the following steps: S5: Dissolve hyaluronic acid (molecular weight of 200,000 to 400,000) in deionized water, add sodium periodate, stir and carry out oxidation reaction for 6 to 24 hours under light-proof conditions and at 25 °C, add ethylene glycol after the reaction for 1 to 2 hours to terminate the oxidation reaction, dialyze the mixed solution obtained in the reaction in deionized water for 3 days, and freeze-dry the mixed solution after the dialysis to obtain the oxidized hyaluronic acid. The ratio of hyaluronic acid, sodium periodate and deionized water is (1.9 to 3.6) g: (2.2 to 3.3) g: 100 mL; the ratio of sodium periodate to ethylene glycol is (2.2 to 3.3) g: (0.43 to 0.64) g; the molecular weight cutoff of the dialysis bag used in dialysis is 6000 to 8000 Daltons.
[0026] More specifically, the method for preparing the carbohydrazide-modified gelatin in step S2 comprises the following steps: S6: Heat gelatin and dissolve it in deionized water, add carbohydrazide, and after it is completely dissolved, add N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole hydrate, and then adjust the solution pH to 5 with hydrochloric acid. Perform amidation reaction at room temperature (25 °C) for 12-24 h. After the reaction, dialyze the product in 0.3 mol / L sodium chloride solution, 25% (v / v) ethanol solution and deionized water for 2 days, 1 day and 4 days, respectively, and finally freeze-dry to obtain the carbohydrazide-modified gelatin. The temperature for heating and dissolving gelatin is 50-70 °C; the ratio of gelatin, carbohydrazide, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, 1-hydroxybenzotriazole hydrate and deionized water is (2.5-3.2) g:(2.0-2.5) g:(0.42-0.48) g:(0.43-0.50) g:100 mL; N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole hydrate are dissolved in 10 mL of deionized water and dimethyl sulfoxide, respectively, and then added dropwise to the gelatin / carbohydrazide mixed solution; the molecular weight cutoff of the dialysis bag used in dialysis is 6000-8000 Daltons.
[0027] At the same time, the present invention also discloses a method for preparing a dynamic hydrogel that can be used immediately. The solution is added to the above-mentioned dynamic micron-sized gel powder, and after complete hydration, an injectable hydrogel in a hydrated state is formed. The ratio of the solution to the dynamic micron-sized gel powder is (5.67~8.09) g:1.0 g. The hydration time is 5~90 min. The above-mentioned solution can be a pure water solution, a PBS solution, a cell culture solution, a protein-containing solution, etc.
[0028] The invention discloses a dynamic micron-sized gel powder and a method for preparing a ready-to-use dynamic hydrogel. The preparation method disclosed in the invention prepares a nanocomposite hydrogel with multiple dynamic bonds cross-linked by doping polydopamine nanoparticles in a hydrogel cross-linked by oxidized hyaluronic acid and carbohydrazide-modified gelatin. Among them, a borate ester bond is formed between borax and oxidized hyaluronic acid, an acylhydrazone bond is formed between carbohydrazide-modified gelatin and oxidized hyaluronic acid, and a hydrogen bond is formed between the polydopamine nanoparticles and the hydrogel network. The synergistic effect of multiple dynamic bonds gives the nanocomposite hydrogel excellent dynamic properties, including injectability, self-healing properties and mechanical properties. Afterwards, the nanocomposite hydrogel is freeze-dried and fully ground to obtain a dynamic micron-sized gel powder. After the gel powder is stored under ambient conditions for 90 days, adding an appropriate amount of solution (deionized water, phosphate buffer solution, cell culture fluid, etc.) can still quickly hydrate to form a dynamic hydrogel and maintain dynamic properties similar to those of the original hydrogel. The present invention proposes a new strategy for preparing dynamic micron-sized gel powder that can be stored for a long time and quickly hydrated to obtain instant dynamic hydrogel, which provides a new idea for solving the problem of cumbersome and time-consuming preparation of dynamic hydrogel and realizing large-scale production of ready-made dynamic hydrogel without cold chain and low cost.
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0030] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0031] Example 1 A method for preparing dynamic micron-sized gel powder comprises the following steps: S1: Synthesis of oxidized hyaluronic acid by sodium periodate oxidation.
[0032] The specific steps are as follows: 7.2 g of hyaluronic acid is dissolved in 240 mL of deionized water, 7.7 g of sodium periodate is added, and the hyaluronic acid molecular weight is 200,000 to 400,000 is stirred for 12 hours under light-proof conditions. Then, 1.488 g of ethylene glycol is added and stirred for 2 hours to terminate the oxidation reaction. The resulting mixed solution is dialyzed in deionized water for 3 days (the molecular weight cutoff of the dialysis bag is 6000 Daltons), and the deionized water is replaced every 8 hours. The dialyzed mixed solution is freeze-dried to obtain oxidized hyaluronic acid.
[0033] S2: Preparation of carbohydrazide-modified gelatin via amidation reaction.
[0034] The specific steps are as follows: 9.0 g of gelatin is heated and dissolved in 300 mL of deionized water, 6.6 g of carbohydrazide is added, and after it is completely dissolved, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole hydrate are added. Among them, 1.35 g of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole hydrate are dissolved in 10 mL of deionized water and dimethyl sulfoxide, respectively, and then added dropwise. Then, the pH of the solution is adjusted to 5 with hydrochloric acid, and the amidation reaction is carried out at room temperature (25 °C) for 12 h. After the reaction, the product is dialyzed in 0.3 mol / L sodium chloride solution, 25% (v / v) ethanol solution and deionized water for 2 days, 1 day and 4 days (the molecular weight cutoff of the dialysis bag is 6000 Daltons), and after the dialysis, the mixed solution is freeze-dried to obtain the carbohydrazide modified gelatin.
[0035] S3: Preparation of protein-loaded polydopamine nanoparticles.
[0036] The specific steps are as follows: 100 mg of bovine serum albumin was dissolved in 10 mL of Tris-HCl buffer (10 mM, pH 8.5). Then 50 mg of dopamine hydrochloride was added to the above protein-containing buffer solution and stirred at room temperature (25 °C) for 12 hours to obtain a black reaction solution. The reaction solution was subjected to ultracentrifugation and washed with deionized water and centrifuged three times. The supernatant was removed and the remaining precipitate was freeze-dried to obtain protein-loaded polydopamine nanoparticles.
[0037] S4: Preparation of multiple dynamically cross-linked nanocomposite hydrogels.
[0038] The specific steps are as follows: dissolving oxidized hyaluronic acid in a phosphate buffer solution with a concentration of 0.1 mol / L and a pH of 7.4 to obtain an oxidized hyaluronic acid solution with a mass percentage of 9 wt%. Ultrasonic dispersion of protein-loaded polydopamine nanoparticles in the hyaluronic acid solution to obtain an oxidized hyaluronic acid solution containing nanoparticles with a mass concentration of 5 mg / mL. Subsequently, dissolving carbohydrazide-modified gelatin in a phosphate buffer solution of borax to obtain a carbohydrazide-modified gelatin / borax solution with a mass percentage of 12 wt%, wherein the concentration of borax is 0.1 mol / L. The oxidized hyaluronic acid solution containing nanoparticles and the carbohydrazide-modified gelatin / borax solution are uniformly mixed in a volume ratio of 1:2.5 to obtain a multiple dynamically cross-linked nanocomposite hydrogel.
[0039] S5: Preparation of dynamic micron-sized gel powder.
[0040] The specific steps are as follows: freeze-dry the multiple dynamic bond cross-linked nanocomposite hydrogel at -80 °C for 72 hours, and then grind it thoroughly until there are no particles visible to the naked eye, so as to obtain a dynamic micron-sized gel powder that can be stored and transported for a long time under ambient conditions.
[0041] The transportation environment conditions of the dynamic micron-sized gel powder are a temperature of 15-25°C and a humidity of 40%RH-70%RH.
[0042] When in use, a proper amount of solution is added to the gel powder under ambient conditions to rapidly hydrate and form a dynamic gel. During the hydration process, the ratio of the added solution to the gel powder is 7.55 g:1.0 g. The rapid hydration time is 60 minutes.
[0043] Example 2 A method for preparing a dynamic micron-sized gel powder, the method differing from Example 1 only in that the mass percentage of the oxidized hyaluronic acid is 3 wt %. The remaining steps are the same as those of Example 1.
[0044] Example 3 A method for preparing a dynamic micron-sized gel powder, the method differing from Example 1 only in that the mass percentage of the oxidized hyaluronic acid is 6 wt %. The remaining steps refer to Example 1.
[0045] Example 4 A method for preparing a dynamic micron-sized gel powder, the method differing from Example 1 only in that the mass percentage of the oxidized hyaluronic acid is 12 wt %. The remaining steps are the same as those of Example 1.
[0046] Example 5 A method for preparing a dynamic micron-sized gel powder, the method differing from Example 1 only in that the mass percentage of the oxidized hyaluronic acid is 15 wt %. The remaining steps are the same as those of Example 1.
[0047] Example 6 A method for preparing a dynamic micron-sized gel powder, the method differing from Example 1 only in that the mass concentration of the protein-loaded polydopamine nanoparticles ultrasonically dispersed in the hyaluronic acid solution is 1 mg / mL. The remaining steps refer to Example 1.
[0048] Example 7 A method for preparing a dynamic micron-sized gel powder, the method differing from Example 1 only in that the mass concentration of the protein-loaded polydopamine nanoparticles ultrasonically dispersed in the hyaluronic acid solution is 2.5 mg / mL. The remaining steps refer to Example 1.
[0049] Example 8 A method for preparing a dynamic micron-sized gel powder, the method differing from Example 1 only in that the mass concentration of the protein-loaded polydopamine nanoparticles ultrasonically dispersed in the hyaluronic acid solution is 10 mg / mL. The remaining steps refer to Example 1.
[0050] Example 9 A method for preparing a dynamic micron-sized gel powder, the method differing from Example 1 only in that the volume ratio of the oxidized hyaluronic acid solution containing nanoparticles to the carbohydrazide-modified gelatin / borax solution is 1:1.5. The remaining steps are as in Example 1.
[0051] Example 10 A method for preparing dynamic micron-sized gel powder, the method differs from Example 1 only in that the volume ratio of the oxidized hyaluronic acid solution containing nanoparticles to the carbohydrazide-modified gelatin / borax solution is 1:2. The remaining steps refer to Example 1.
[0052] Embodiment 11 A method for preparing dynamic micron-sized gel powder, the method differs from Example 1 only in that the ratio of the amount of solution added in the hydration process to the amount of gel powder is 5.67 g:1.0 g. The remaining steps refer to Example 1.
[0053] Example 12 A method for preparing dynamic micron-sized gel powder, the method differs from Example 1 only in that the ratio of the amount of solution added in the hydration process to the amount of gel powder is 6.69 g:1.0 g. The remaining steps refer to Example 1.
[0054] Embodiment 13 A method for preparing dynamic micron-sized gel powder, the method differs from Example 1 only in that the ratio of the amount of solution added in the hydration process to the amount of gel powder is 9.20 g:1.0 g. The remaining steps refer to Example 1.
[0055] Embodiment 14 A method for preparing dynamic micron-sized gel powder, the method differs from Example 1 only in that the ratio of the amount of solution added in the hydration process to the amount of gel powder is 10.11 g:1.0 g. The remaining steps refer to Example 1.
[0056] Embodiment 15 A method for preparing dynamic micron-sized gel powder, the method differs from Example 1 only in that the duration of the hydration process is 90 minutes. The remaining steps refer to Example 1.
[0057] The structure of the oxidized hyaluronic acid and carbohydrazide modified gelatin prepared in Example 1 was characterized by infrared spectroscopy. Figure 2A As shown in the infrared spectrum of oxidized hyaluronic acid, 1735 cm -1 The peak at 1655 cm is the C=O stretching vibration peak of the aldehyde group, indicating that sodium periodate successfully oxidized the hydroxyl group of hyaluronic acid to the aldehyde group. -1 、1543 cm -1 and 1240 cm -1 The increase in the peaks at 1655 cm -1 is the C=O stretching vibration peak of amide band I, 1543 cm -1 is the in-plane NH bending vibration peak of amide band II, 1240 cm -1 The peak of CN stretching vibration of amide band III was confirmed by infrared analysis. The successful preparation of oxidized hyaluronic acid and carbohydrazide modified gelatin was confirmed.
[0058] The structures of the nanocomposite hydrogel and protein-loaded polydopamine nanoparticles prepared in Example 1 were characterized by infrared spectroscopy. Figure 2B As shown in the infrared spectrum of the nanocomposite hydrogel, the 1735 cm −1 The disappearance of the C=O stretching vibration peak at 1640 cm -1 The characteristic peaks attributable to C=N stretching vibration were observed at 1333 cm -1 and 1400 cm -1 The characteristic peak of asymmetric stretching vibration of BOC was observed at 4 O 72- ) successfully reacted with the hydroxyl groups on the oxidized hyaluronic acid chains to form borate ester bonds. In addition, the hydrogel -1 The -OH stretching vibration peak at 1390 cm indicates the presence of hydrogen bonding in the polymer network. In order to confirm the loading of BSA on polydopamine nanoparticles, the infrared spectra of the two were compared. -1 ) weakened, 1225 cm -1 CN stretching vibration at 1150 cm -1 The relative enhancement of the SN stretching vibration peak at indicates that polydopamine nanoparticles and bovine serum albumin were combined through Michael addition under alkaline conditions.
[0059] The hydrogels with different contents of polydopamine nanoparticles prepared in Example 1 were made into cylindrical samples (12 mm in diameter and 4 mm in height) and subjected to compression performance tests. Figure 3 As shown in the figure, when the doping amount of polydopamine nanoparticles increases from 0 mg / mL to 1.0, 2.5 and 5.0 mg / mL, the compressive stress of the hydrogel increases from 229.51 kPa to 272.65, 354.90 and 385.47 kPa, and the corresponding compression modulus gradually increases from 3.94 kPa to 4.83, 6.80 and 11.37 kPa. However, when the doping amount of polydopamine nanoparticles increases further, the excess polydopamine nanoparticles occupy more functional groups (hydroxyl and carboxyl groups) on the polymer chain, resulting in a decrease in the dynamic covalent bonds generated between the biomacromolecules, resulting in a decrease in the mechanical properties of the hydrogel. The above results show that when an appropriate amount of polydopamine nanoparticles is doped, the multiple dynamic bonds (acylhydrazone bonds, borate bonds and hydrogen bonds) formed between the biomacromolecules and the polydopamine nanoparticles can give the hydrogel good mechanical properties.
[0060] The macroscopic self-healing performance of the nanocomposite hydrogel prepared in Example 1 was tested. Figure 4A As shown in the figure, two identical cylindrical hydrogels were cut into equal halves and quarters, respectively, and then the hydrogel slices were assembled into hydrogel discs. Then, after healing at 37 °C without external intervention for 1 hour, the boundaries between the hydrogel slices became blurred. At the same time, the healed hydrogel was able to withstand the stretching of the tweezers and maintain integrity after deformation. The results show that the nanocomposite hydrogel has good macroscopic self-healing properties.
[0061] The hydrogels with different contents of polydopamine nanoparticles prepared in Example 1 were cut in the middle and placed at 37 °C for 1 h for compression test. The self-healing efficiency of the hydrogel was expressed by calculating the ratio of the compression modulus of the hydrogel before and after self-healing. The self-healing efficiency of the hydrogel was calculated using the following formula:
[0062] Where S h is the compression modulus of the hydrogel after self-healing, S o is the compression modulus of the original hydrogel.
[0063] like Figure 4B As shown in the figure, as the content of polydopamine nanoparticles increased from 0 to 5 mg / mL, the self-healing efficiency of the hydrogel gradually increased. This is because hydrogen bonds were formed between the polydopamine nanoparticles and the oxidized sodium alginate and carbohydrazide-modified gelatin, which improved the self-healing efficiency of the hydrogel.
[0064] The injectability test of the nanocomposite hydrogel prepared in Example 1 was performed. Figure 5A As shown, the hydrogel was injected through an 18-gauge needle, and the extruded gel particles healed and reshaped in the mold to form a T-shaped hydrogel. The reshaped hydrogel can be picked up with tweezers and still maintains its original shape after being immersed in phosphate buffer solution (pH 7.4, 37 °C) for 48 h, demonstrating that the nanocomposite hydrogel has good stability under physiological conditions.
[0065] The viscosity response test was performed on the nanocomposite hydrogel prepared in Example 1. Figure 5B As shown in the figure, the viscosity of the hydrogel decreases with the increase of shear rate, which is due to the shear fracture of the dynamic polymer network caused by the shear force, and the hydrogel sample exhibits shear thinning behavior. This result shows that the nanocomposite hydrogel has excellent injectability.
[0066] The gel powder prepared in Example 1 was observed by scanning electron microscopy. Figure 6 As shown, the high-magnification scanning electron microscope image shows that the ground gel powder presents a micron-sized block structure, indicating that grinding the freeze-dried nanocomposite hydrogel can obtain gel powder with a size of micron level.
[0067] The hydration process of the dynamic micron-sized gel powder prepared in Example 1 was observed. Figure 7As shown in the figure, after the phosphate buffer solution was added, the dynamic micron-sized gel powder quickly absorbed water and rehydrated to form a complete dynamic gel, which can be picked up with tweezers and withstand the pressure of fingers. At the same time, the hydrated dynamic gel can not only maintain continuity during the injection process, but also be reshaped into a complete four-leaf clover sample after being injected into the mold and healing for 1 hour. The above results show that the hydrated dynamic gel obtained by hydrating the gel powder inherits the excellent dynamic properties of the original hydrogel, including injectability, self-healing and mechanical properties.
[0068] The dynamic gel obtained by hydrating the gel powder in Example 1 was observed by scanning electron microscopy. Figure 8 As shown, high-magnification scanning electron microscope images show that the hydrated dynamic gel presents a clear three-dimensional network structure, indicating that the micron-sized gel powder can still be hydrated to form a hydrogel after long-term storage.
[0069] The dynamic gel obtained by hydrating the gel powders stored for different lengths of time in Example 1 was tested for compression performance. Fig. 9 As shown in the figure, the compressive stress and compression modulus of the dynamic gel obtained by hydrating the unstored gel powder are 285.42 kPa and 11.17 kPa, respectively, which are very close to the mechanical properties of the original nanocomposite hydrogel. In addition, the mechanical properties of the dynamic gel obtained by hydrating the gel powder stored under ambient conditions for 90 days only slightly decreased (compressive stress: 275.50 kPa, compression modulus: 9.79 kPa). The above results show that the dynamic gel obtained by hydrating the gel powder stored under ambient conditions for a long time can retain mechanical properties similar to those of the original hydrogel.
[0070] The dynamic gel obtained by hydrating the gel powder stored for 90 days in Example 1 was tested for injectability. Fig.10 As shown, the hydrated dynamic gel was injected through an 18-gauge needle, and the extruded gel particles could be picked up with tweezers after healing and reshaping in the letter mold. Moreover, after being immersed in phosphate buffer solution (pH 7.4, 37 °C) for 48 h, the hydrated dynamic gel was still able to maintain its original shape, once again proving that the dynamic gel obtained by hydrating the gel powder stored for a long time can retain dynamic properties similar to those of the original hydrogel.
[0071] The protein-loaded polydopamine nanoparticles prepared in Example 1 were characterized by UV-visible spectroscopy. Fig.11A As shown, compared with the UV-visible absorption spectrum of polydopamine nanoparticles, the phenolic hydroxyl absorption peak of protein-loaded polydopamine nanoparticles at 280 nm was relatively weakened, indicating that the phenolic hydroxyl groups on the surface of polydopamine nanoparticles were involved in the binding with proteins.
[0072] The protein-loaded polydopamine nanoparticles prepared in Example 1 were observed by scanning electron microscopy, and the zeta potential and particle size were tested. Fig. 11B As shown in the figure, polydopamine nanoparticles are uniformly spherical with an average diameter of about 460 nm. After embedding bovine serum albumin, the morphology of the protein-loaded polydopamine nanoparticles becomes irregular, and the average particle size increases to 540 nm ( Fig.11D The zeta potential of polydopamine nanoparticles dispersed in phosphate buffer solution (pH 7.4) is -5.01 mV. Since bovine serum albumin is negatively charged in phosphate buffer solution at pH 7.4, the zeta potential of polydopamine nanoparticles loaded with protein is significantly reduced to -11.60 mV ( Fig. 11C ). The above results prove that polydopamine nanoparticles can bind to bovine serum albumin through Michael addition reaction, which leads to an increase in the particle size of polydopamine nanoparticles and a decrease in zeta potential.
[0073] The protein cumulative release performance test was performed on the dynamic gel obtained by hydrating the gel powder stored for different times in Example 1. Fig.12 As shown in the figure, the original hydrogel achieved 19 days of in vitro protein release at a slower release rate, while the sustained release time of the dynamic gel obtained by hydrating the gel powder with different storage times was shortened, but it could still achieve 15 days of in vitro release. In addition, there was no significant difference in the release rate and maximum cumulative release amount of the dynamic gel obtained by hydrating the gel powder with different storage times. The above results show that the protein release performance of the hydrated dynamic gel is not related to the storage time of the dynamic micron-sized gel powder.
[0074] The hydrogel prepared in Example 1 was subjected to cytotoxicity testing. The hydrogel extract was co-cultured with mouse L929 fibroblasts, and the cell compatibility of the hydrogel was evaluated by live / dead cell staining and CCK-8 method. Fig.13A As shown in the figure, the Live / Dead staining kit was used to detect the effect of L929 fibroblasts co-cultured with the hydrogel extract for 24, 48 and 72 h. It can be seen that a large number of live cells (green fluorescence) appeared in both the control group and the experimental group cultured with the hydrogel extract, but almost no dead cells (red fluorescence) appeared. At the same time, the number of live cells gradually increased with the extension of the culture time. Fig. 13B As shown in the figure, the survival rate of L929 fibroblasts was calculated by CCK-8 method to further evaluate the toxicity of the hydrogel. After 24, 48, and 72 h of culture, there was no significant difference in the cell survival rate between the fibroblasts cultured in the hydrogel extract and the control group, all of which were higher than 90%.
[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing dynamic micron-sized gel powder, characterized in that: The following steps are involved: S1: dissolving dopamine hydrochloride in a Tris-HCl buffer containing a protein to be carried, stirring the reaction, and preparing protein-loaded polydopamine nanoparticles; S2: dissolving oxidized hyaluronic acid in a phosphate buffer solution, and adding the protein-loaded polydopamine nanoparticles to obtain an oxidized hyaluronic acid solution containing nanoparticles; dissolving carbohydrazide-modified gelatin in a phosphate buffer solution containing borax to obtain a carbohydrazide-modified gelatin / borax solution; S3: uniformly mixing the oxidized hyaluronic acid solution and the carbohydrazide-modified gelatin / borax solution to prepare a nanocomposite hydrogel based on multiple dynamic bond crosslinking; S4: freeze-drying and grinding the multiple dynamic bond cross-linked nanocomposite hydrogel to obtain the dynamic micron-sized gel powder.
2. The method for preparing a dynamic micron-sized gel powder according to claim 1, characterized in that: In step S1, the mass concentration of dopamine hydrochloride is 0.2-10 mg / mL; the mass concentration of the protein to be carried in the Tris-HCl buffer is 0.5-3 mg / mL; during the stirring reaction, the stirring speed is 100-600 rpm, and the reaction time is 8-24 hours.
3. The method for preparing a dynamic micron-sized gel powder according to claim 1, characterized in that: In step S2, the preparation of the carbohydrazide modified gelatin is as follows: heating gelatin to dissolve in deionized water, adding carbohydrazide, and adding N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole hydrate after the gelatin is completely dissolved, and then adjusting the pH value of the system to 5, performing an amidation reaction at room temperature, and finally dialyzing and freeze-drying to obtain the carbohydrazide modified gelatin; the mass ratio of the gelatin, carbohydrazide, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, and 1-hydroxybenzotriazole hydrate is (2.5~3.2):(2.0~2.5):(0.42~0.48):(0.43~0.50); the time of the amidation reaction is 12~24 h.
4. The method for preparing a dynamic micron-sized gel powder according to claim 1, characterized in that: In step S2, the concentrations of the oxidized hyaluronic acid and the carbohydrazide-modified gelatin / borax solution are 3 wt% to 15 wt% and 10 wt% to 12 wt%, respectively.
5. The method for preparing a dynamic micron-sized gel powder according to claim 1, characterized in that: In step S3, the volume ratio of the oxidized hyaluronic acid solution containing nanoparticles to the carbohydrazide-modified gelatin / borax solution is 1:(1.5-2.5).
6. The method for preparing a dynamic micron-sized gel powder according to claim 1, characterized in that: In step S3, the gelation temperature of the nanocomposite hydrogel is 37 °C, and the gelation time is 5 to 30 s.
7. A dynamic micron-sized gel powder, characterized in that: Prepared by the method according to any one of claims 1 to 6; the average pore size of the gel powder is 50 μm.
8. A method for preparing a ready-to-use dynamic hydrogel, characterized in that: The solution is added to the dynamic micron-sized gel powder as claimed in claim 7, and after complete hydration, the instant dynamic hydrogel is formed.
9. The method for preparing a ready-to-use dynamic hydrogel according to claim 8, characterized in that: The ratio of the solution to the dynamic micron-sized gel powder is (5.67-8.09) g:1.0 g.
10. The method for preparing a ready-to-use dynamic hydrogel according to claim 8, characterized in that: The hydration time is 5 to 90 min.
Citation Information
Patent Citations
Injectable composite hydrogel capable of promoting wound healing and reducing scar formation as well as preparation method and application of injectable composite hydrogel
CN115678048A
Full-micromolecule self-gelling freeze-dried powder and preparation method thereof
CN117599002A
Self-healing injectable nano-composite hydrogel of high-strength natural macromolecules based on multiple dynamic bonds and preparation method of self-healing injectable nano-composite hydrogel
CN117771429A
Double-protein sequential delivery self-healing injectable hydrogel system and preparation method thereof
CN118059033A
Dynamic Covalent Hydrogels, Precursors Thereof and Uses Thereof
US20230181462A1